2008
DOI: 10.1371/journal.pone.0001649
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Domes Encapsulate Adherent Neutrophils and Minimize Increases in Vascular Permeability in Paracellular and Transcellular Emigration

Abstract: Local edema, a cardinal sign of inflammation associates closely with neutrophil emigration. Neutrophil emigration has been described to occur primarily through endothelial junctions (paracellular) and more rarely directly through endothelial cells (transcellular). Recently, we reported that unlike in wild-type (wt) mice, Mac-1-/- (CD11b) neutrophils predominantly emigrated transcellularly and was significantly delayed taking 20–30 min longer than the paracellular emigration (wt). In the present study we noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 29 publications
7
71
0
Order By: Relevance
“…These patients suffer from recurrent bacterial infections. b 2 integrin Mac-1 favors paracellular migration of leucocytes and in Mac-1 -/ -(CD11b) mice, neutrophils predominantly emigrate transcellularly (through endothelial cells) and were delayed by 20-30 min compared with the more rapid paracellular emigration route (351). In contrast to b 2 integrins, the b 1 integrin family mediates neutrophil adhesion to extracellular matrix proteins such as fibronectin and VLA4 or a 4 b 1 integrin.…”
Section: B Integrinsmentioning
confidence: 99%
“…These patients suffer from recurrent bacterial infections. b 2 integrin Mac-1 favors paracellular migration of leucocytes and in Mac-1 -/ -(CD11b) mice, neutrophils predominantly emigrate transcellularly (through endothelial cells) and were delayed by 20-30 min compared with the more rapid paracellular emigration route (351). In contrast to b 2 integrins, the b 1 integrin family mediates neutrophil adhesion to extracellular matrix proteins such as fibronectin and VLA4 or a 4 b 1 integrin.…”
Section: B Integrinsmentioning
confidence: 99%
“…92,93 This appears to occur despite the fact that endothelial cells can extend projections to envelop the migrating neutrophils, forming endothelial domes, with the leakage response resulting from the transfer of entrapped plasma proteins within the "dome." 83,94 It has also been reported that the endothelial barrier dysruption caused by transmigrating leukocytes are detected by the endothelial cells as a release of isometric tension, which results in protective actin remodeling that is dependent on the production of reactive oxygen species. 95 Furthermore, the results of a recent study reveal that extravasating leukocytes deposit microparticles on the subendothelium during their passage through the junctions and that the microparticle deposition serves to maintain barrier function; inhibition of neutrophil-derived microparticle formation resulted in dramatically increased vascular leakage.…”
Section: Leukocytes and Endothelial Barrier Functionmentioning
confidence: 99%
“…transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures. 14,[67][68][69][70][71] The names were based on the hypothesized function or morphology of these structures. Work of Carman and coworkers showed that these structures, that formed both during para-and transcellular diapedesis (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%